Surveying and screening South African entomopathogenic nematodes for the control of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann). (March 2018) - James, Monique; Malan, Antoinette Paula; Addison, Pia
Abstract: The polyphagous Mediterranean fruit fly or Medfly, Ceratitis capitata, which is an economically important pest species to fruit growers globally, including those in South Africa, spends part of its life cycle in the soil as a final instar larva and pupa. Entomopathogenic nematodes (EPNs) of the families Steinernematidae and Heterorhabditidae are insect-killing parasites that occur naturally in soils worldwide. The main aim of this study was to identify local, South African EPN species highly pathogenic against Medfly larvae entering the soil to pupate. Eighty soil samples were taken from fruit orchards in the Western and Northern Cape provinces of South Africa, and baited with susceptible host insects, including the target pest. The identity of the EPNs isolated was verified using molecular techniques. The pathogenicity of five local EPN species were screened in the laboratory by inoculating single third instar Medfly larvae with 100 infective juveniles (IJs) in 50 μl of water. After 48 h, high Medfly larval mortality was obtained, with no significant difference being found between the nematode species, and the experiment was therefore repeated at a lower concentration of infective juveniles. The pathogenicity of the most virulent EPN, Heterorhabditis noenieputensis, along with Steinernema yirgalemense, was further tested by inoculating 100 ml of sterilised sand with 2000 IJs. After 24 h, 10 third instar Medfly larvae were added to the sand. High mortality of Medfly larvae, using H. noenieputensis, promises well for local EPN species, which could be used as a biological control agent against the Medfly, within an integrated pest management system. Graphical abstract: Highlights: Heterorhabditis noenieputensis and Steinernema yirgalemense showed high virulence. No fully formed Medfly pupae were infected by local entomopathogenic nematodes. In sand, H. noenieputensis infected Medfly larvae, which died as infected pupae. Heterorhabditis noenieputensis is 14 times more potent than S. yirgalemense.